Growth of Ferrobacillus ferrooxidans on Organic Matter - Shafia, Fred (1969)
Following a brief adaptation period to glucose, Ferrobacillus ferrooxidans was grown on glucose, mannitol, several other sugars, and a few amino acids in the absence of an oxidizable iron source. Prolonged growth on an organic substrate free from iron rendered the organism obligately organotrophic. The growth rate of the bacterium was greater in heterotrophic culture; the doubling time was approximately 4.5 hr on glucose. The bacterium retained its acidophilic properties during adaptation and growth on glucose and would not grow in neutral or slightly alkaline media. Addition of p-aminobenzoic acid was necessary for abundant growth of the cells on glucose. Of the eight strains of Fe(++)-oxidizing bacteria studied, only two strains grew on glucose in a nondialyzed system. The results of manometric studies are discussed with regard to metabolic efficiency of organic matter in this organism.